La motivación y su influencia en el rendimiento escolar de los estudiantes del séptimo año de educación básica de la Unidad Educativa Hermano Miguel de la ciudad de Machala año lectivo 2010-2011. - Acosta Palas, Judith Esther (2011)
It consists of five chapters, which are the same. The problem under study, Theoretical Framework, Methodology, Analysis and Interpretation of the results of field research and the proposed intervention.